Catalisadores hierárquicos Fe2O3/ZSM-5: efeito da mesoporosidade do suporte na atividade de nanopartículas de óxido de ferro em reação foto-Fenton - Drumm, Fernanda Caroline (2016)
This work evaluated the synthesis of hierarchical Fe2O3/ZSM -5 catalysts and their catalytic activity in the degradation of azo dye Yellow Tartrazine in photo-Fenton reaction. The chitin powder was applied as a mesopore template in the gel synthesis of ZSM -5, being removed after its crystallization by heat treatment. Removal of chitin generated voids, resulting in the formation of meso and macropores in the microporous structure of ZSM -5.The deposition of iron oxide nanoparticles on the zeolite was performed using the impregnation technique. Through the XRD analysis, it was observed that zeolites obtained showed typical MFI structure and, as higher the amount of chitin added in preparation of the synthesis gel, the lower the crystallinity of the material. Furthermore, the increase in chitin contents promoted a wide distribution range of meso and macropores in the zeolite, resulting in an increase in average pore size, as well as a larger volume, found, through analysis of N2 adsorption / desorption. Through the micrograph analysis of the obtained catalysts, it can be seen better dispersion of iron oxide on the hierarchical zeolite, which was attributed to higher porosity of the surface, resulting in higher anchor points for the iron oxide be deposited, and also in the formation of smaller sizes of clusters on the support. Unlike what was observed in the hierarchical support, the dispersion of iron oxide was less homogeneous in the microporous zeolite, resulting in a larger size of agglomerates on its surface. These characteristics in the structure of the catalysts had a strong influence on the catalytic activity of dye degradation by photo-Fenton process, where the hierarchical catalysts showed far superior results to catalysts with microporous surface as well as iron oxide unsupported, with the removal 99 %, 33 %, 10 % respectively. This enhancement in the reaction is due to the increased amount of active sites dispersed in the hierarchical catalyst available for decomposition of H2O2 and for formation of hydroxyl radicals, increasing the degradation rate of the dye. The optimum conditions for further removal of Yellow Tartrazine dye, used as a pollutant model in this work were determined by response surface methodology, which were pH 2.7, amount of catalyst of 0.4 g / L and 2 times the stoichiometric amount of H2O2 needed to complete mineralization of the colorant, promoting the removal of 99% of color of solution by 30 minutes of reaction.